A CLINICAL CASE OF MOYAMOYA DISEASE IN A PREGNANT WOMAN - Алена Викторовна Робул; Ольга Владимировна Евдокимова; Константин Сергеевич Колобников; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Анна Александровна Железная; Елена Владимировна Рудаева; Полина Никитична Мраморнова; Кира Борисовна Мозес (The Publishing House Medicine and Enlightenment, 2022)
Moyamoya disease (a puff of smoke, fog) develops, as a rule, in children and adults of working age and consists in a slowly progressive narrowing of the lumen of the intracranial segments of the internal carotid artery, the initial sections of the anterior and middle cerebral arteries up to their complete occlusion. With a compensatory purpose, many small collaterals have time to form in the brain, which visually resemble a ball of smoke on brain angiograms. My-my disease is extremely rare (in Europe, USA, Japan, Africa), its prevalence even in the most endemic areas is only 0.35 per 100,000 population. This article describes a rare clinical case of Moyamoya disease in a pregnant woman. Considering the optimal chosen management tactics of the patient, a favorable outcome was obtained for the woman and fetus.